4. PEMBERDAYAAN PEREMPUAN DAN KETAHANAN PANGAN DI TINGKAT KELUARGA - Rodhiyah, Rodhiyah (Faculty of Social and Political Sciences Diponegoro University, 2009)
Poverty is a serious challenge in Indonesia, and most of the poor segments of the people are women. Poverty problems are closely related with food shoriage and food security problem. When poor women faces various social problems, women empowerment is one among the must be solutions. Women empowerment efforts can be started from economic side to enable them meeting family needs, and then gender strengthening by opening women access to meet women special needs such as education and health to enhance these women quality, as well as the quality of their families, state and nation. Many factors influence food security in the family, covering educational level, income, food consumption behaviour, family food habit, and others. Family plays an important role in the food security issue in each household. When a family could well meet its food needs, both quantitatively and qualitatively, this family’s life quality will be getting better, including its women members.